2008
DOI: 10.1016/j.jneumeth.2007.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Detection of full-length and truncated neurokinin-1 receptor mRNA expression in human brain regions

Abstract: We have applied a newly developed SYBR green based real-time RT-PCR assay for quantification of full-length and truncated neurokinin-1 receptor (NK1R) mRNA expression in 9 regions of human brain tissues obtained from 23 subjects who died with no evidence of neurological or neurodegenerative disease. The following brain regions were examined: cingulate cortex, cerebellum, nucleus accumbens, caudate nucleus, putamen, pons, hippocampus, locus coeruleus, and basal ganglia. The SYBR green based-real-time PCR was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 29 publications
0
45
0
Order By: Relevance
“…We have recently applied a SYBR green-based real-time RT-PCR for quantification of fulllength and truncated NK1R mRNA in 9 regions of human brain tissues [8]. The findings suggest that the expression levels and function of the full-length NK1R are anatomic region-dependent [8]. We demonstrated that truncated NK1R has higher expression levels than that of the full-length NK1R, and that there are significant differences in expression in different brain regions [8].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…We have recently applied a SYBR green-based real-time RT-PCR for quantification of fulllength and truncated NK1R mRNA in 9 regions of human brain tissues [8]. The findings suggest that the expression levels and function of the full-length NK1R are anatomic region-dependent [8]. We demonstrated that truncated NK1R has higher expression levels than that of the full-length NK1R, and that there are significant differences in expression in different brain regions [8].…”
Section: Introductionmentioning
confidence: 95%
“…The binding and signaling properties of the truncated receptor or mutants have been compared with those of the full-length receptor that is expressed in several cell systems and differences have been observed [1,[5][6][7]. We have recently applied a SYBR green-based real-time RT-PCR for quantification of fulllength and truncated NK1R mRNA in 9 regions of human brain tissues [8]. The findings suggest that the expression levels and function of the full-length NK1R are anatomic region-dependent [8].…”
Section: Introductionmentioning
confidence: 99%
“…A splice variant of human NK-1R has an exon 5 deletion, which yields a truncated NK-1R with 311 residues that lacks the majority of the intracellular C-tail (37). The truncated NK-1R was identified in human monocytes and macrophages (38), brain regions (cortex, cerebellum) (39) and colonic epithelial cells of colitis-associated cancer (40).…”
Section: Discussionmentioning
confidence: 99%
“…However, differentiation of these cells towards a macrophage phenotype with a phorbol ester leads to the expression of both isoforms [64], which could modulate cellular activity. Different brain regions appear to exhibit different patterns of NK 1 receptor pre-mRNA alternative splicing, with expression of the truncated NK 1 receptor often being greater than that of the full-length variant [64], which could result in effects on pain perception.…”
Section: Alternative Splicing Of Gpcr In Other Pathophysiological Conmentioning
confidence: 99%
“…[59][60][61][62][63][64] Neurokinin receptor 2 Exon exclusion Impaired ligand binding and signalling [65,66] Neuropeptide S receptor (GPRA) Alternative C-terminal exons, trancation Intracellular localization of truncated isoform [67] Opioid receptors Several Various Reviewed in [68] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 Overview of GPCRs encoded by more than one exon. In the "pre-human genome era" it was assumed that more than 90% of human GPCRs were intronless [15].…”
Section: Closing Remarksmentioning
confidence: 99%